THE GENERAL DATA PROTECTION LAW AND THE INTERNET OF THINGS: : NEEDS AND CHALLENGES IN THE BRAZILIAN CONTEXT (REMUNOM, 2024)
The Internet of Things (IoT) is transforming digital connectivity in Brazil and raising new challenges for the protection of personal data. This article investigates how the General Data Protection Law (LGPD) addresses privacy and security issues in the IoT era, analyzing the effectiveness of Brazilian legislation in this context. The introduction highlights the urgency of adapting the LGPD to address the complexities associated with the mass and automated data collection by IoT devices. The development section of the article explores the evolution of data protection standards, focusing on the LGPD and its limitations in the face of IoT. Although the LGPD represents a significant advancement in data protection in Brazil, it still struggles to adapt to the new demands of IoT, including continuous data collection and the need to ensure information security. The study aims to evaluate the adequacy of the LGPD for the IoT reality and to suggest improvements for the legislation. The methodology employed is a narrative-descriptive bibliographic review, based on relevant books and scientific articles. This approach allows for a critical analysis of the interactions between IoT and the LGPD, providing a detailed view of regulatory issues in the Brazilian context. The results indicate that the LGPD requires specific adjustments to effectively address the challenges posed by IoT. It is recommended to create additional regulations and integrate data protection practices from the design of the devices. The conclusion underscores the importance of developing specific regulations for IoT in Brazil and promoting ongoing dialogue among regulators, industry, and society. This effort will ensure that technological innovation advances in harmony with the protection of citizens' personal data. Keywords: Internet of Things (IoT). General Data Protection Law (LGPD). Personal Data Protection. Information Security.